A method for preparing melamine-polyimide composite fiber by dry spinning
By adding a water-soluble polyamide salt solution to the melamine resin as a modifier, the melamine-polyimide composite fiber was prepared, which solved the problems of poor stability, poor spinning and thermal stability of the melamine fiber, and improved the temperature resistance, flame retardancy and toughness of the fiber.
Patent Information
- Application Number
- CN202310223359.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-03-09
AI Technical Summary
Melamine fibers have problems such as poor stability, poor spinning, brittle quality, poor toughness and poor thermal stability at high temperatures.
During the reaction of the melamine resin, a water-soluble polyamide salt solution was added as a modifier, and a high molecular weight and uniformly stable melamine-polyimide spinning solution was obtained through joint reaction. The melamine-polyimide primary fiber was obtained by dry spinning, and the melamine-polyimide primary fiber was obtained by high-temperature heat curing to obtain melamine-polyimide protofilament.
It improves the stability of the spinning liquid, enhances the temperature resistance, flame retardancy and toughness of the fibers, and has a high glass transition temperature, effectively improving the high-temperature thermal stability and flame retardancy of melamine fibers.
Smart Images

Figure BDA0004117622950000141 
Figure HDA0004117622960000011 
Figure HDA0004117622960000012
Abstract
Description
1. Technical field:
[0001] The invention relates to the technical field of flame retardant fiber manufacturing, and in particular to a method for preparing melamine-polyimide composite fibers by dry spinning. 2. Background technology:
[0002] Melamine resin is a widely used thermosetting amino resin made from melamine through methylation and polycondensation. It can be made into fibers, molding compounds and laminates, etc. The product has good high temperature resistance and flame retardant properties.
[0003] Melamine fiber is obtained from melamine resin through a certain spinning process. It is a new type of halogen-free flame-retardant fiber. Due to its extremely low thermal conductivity, high residual carbon rate, no droplets, no toxic smoke in flames or high temperatures, and low shrinkage, it is a structural flame-retardant fiber with permanent flame retardancy, which has attracted widespread attention.
[0004] However, melamine fiber is a thermosetting polymer, and curing is achieved through cross-linking of methylene or dimethylene ether bonds. The two ends of the methylene are connected to triazine rings with great steric hindrance, and multiple methylene and triazine rings are intertwined, resulting in poor spinning performance. The fiber after fiberization is hard, difficult to bend, and almost no toughness. Due to these problems, the modification of melamine fiber has become the research focus of technicians.
[0005] As a high-performance engineering plastic, polyimide (PI) is widely used in aerospace, electrical insulation, atomic energy industry, national defense construction, environmental industry, protection industry, medical and health care and other technical fields with harsh conditions because of its excellent heat resistance, dielectric properties, low temperature resistance and radiation resistance. Polyimide fiber is a new type of high-performance organic fiber. It has broad market prospects due to its high strength and modulus, low dielectric, high and low temperature resistance, radiation resistance and flame retardancy. The decomposition temperature of polyimide fiber is about 500°C. Even if it is used continuously at a high temperature of 250°C, it will not physically degrade. However, due to the high production cost of polyimide, the variety of raw materials and the immature production process, the civilian field and industrial production of polyimide fiber are not widespread. 3. Summary of the invention:
[0006] The technical problem to be solved by the present invention is: in view of the shortcomings of the above-mentioned melamine fibers, the present invention provides a method for preparing melamine-polyimide composite fibers by dry spinning. In the reaction process of the melamine resin, a water-soluble polyamic acid salt solution is added as a modifier, and a high molecular weight and uniform and stable melamine-polyimide spinning solution is obtained by a joint reaction. The spinning solution is subjected to dry spinning to obtain melamine-polyimide primary fibers, and melamine-polyimide precursor fibers are obtained by high-temperature thermal curing. The present invention improves the stability of the spinning solution by changing the molecular chain structure of the melamine resin, and enhances the temperature resistance, flame retardancy and toughness of the fiber.
[0007] In order to solve the above problems, the technical solution adopted by the present invention is:
[0008] The present invention provides a method for preparing melamine-polyimide composite fibers by dry spinning, the preparation method comprising the following steps:
[0009] a. Dissolve a diamine substance in an organic solvent, add a dianhydride substance after it is fully dissolved to react, control the reaction temperature to be 0°C, and the reaction time to be 10 to 30 minutes; add melamine after the reaction, and continue to react at the reaction temperature for 2 to 3 hours; then add a base to make the polyamic acid undergo a salt-forming reaction, adjust the pH of the resulting reaction solution to 8 to 9, and continue to react for 1 hour to obtain a water-soluble polyamic acid salt solution after the reaction;
[0010] b. Add melamine, paraformaldehyde and deionized water into a reactor, and add sodium hydroxide aqueous solution to adjust the pH of the reaction solution to 8-9, and then heat to 85-95° C. for reaction. After the reaction solution reaches a clear state, 5-20 minutes later, a melamine resin is obtained; then, the water-soluble polyamic acid salt solution obtained in step a is added according to the mass ratio of melamine resin to polyamic acid salt effective component of 7-9:1-3, and the reaction is continued at this temperature for 10-20 minutes. After the reaction is completed, the temperature is cooled in an ice water bath to obtain a melamine-polyimide spinning solution;
[0011] c. Degassing the melamine-polyimide spinning solution obtained in step b, adding it into a dry spinning machine after degassing to extrude it into fibers through a spinneret, and then removing the solvent through hot air in the spinning tunnel and winding it with a fiber collecting machine to obtain melamine-polyimide nascent fibers; placing the obtained nascent fibers in an oven under nitrogen atmosphere for imidization treatment, and naturally cooling them to room temperature after treatment to obtain melamine-polyimide composite fibers.
[0012] According to the above-mentioned method for preparing melamine-polyimide composite fibers by dry spinning, the diamine substance in step a is at least one of 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, p-phenylenediamine, 4,4'-diaminodiphenylmethane, m-phenylenediamine and o-phenylenediamine;
[0013] The dianhydride substance is at least one of 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, pyromellitic dianhydride, 1,2,3,4-butane tetracarboxylic dianhydride and 3,3,4,4-diphenyl sulfone tetracarboxylic dianhydride;
[0014] The organic solvent is any one of N-dimethylformamide, N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone;
[0015] The base is at least one of triethylamine, aqueous ammonia and triethanolamine.
[0016] According to the above-mentioned method for preparing melamine-polyimide composite fibers by dry spinning, in step a, the molar ratio between the amino group (-NH2) of the diamine substance, the amino group (-NH2) in melamine and the anhydride (R-CO-O-CO-R') in the dianhydride substance is 0.95-0.97:0.07-0.09:1, and the amount of organic solvent added accounts for 70-80% of the reaction system.
[0017] According to the above-mentioned method for preparing melamine-polyimide composite fibers by dry spinning, the molar ratio between melamine and paraformaldehyde in step b is 1:2.3-2.8; the amount of deionized water added is 25-30% of the total mass of the reaction system; and the mass percentage concentration of the sodium hydroxide aqueous solution is 20-25%.
[0018] According to the above-mentioned method for preparing melamine-polyimide composite fibers by dry spinning, the degassing method in step c is vacuum static degassing, and the vacuum degree is 0.04-0.06 MPa.
[0019] According to the above-mentioned method for preparing melamine-polyimide composite fibers by dry spinning, the rotation speed of the metering pump of the dry spinning machine in step c is 30 to 40 r / min.
[0020] According to the above-mentioned method for preparing melamine-polyimide composite fibers by dry spinning, the aperture of the spinneret in step c is 0.1-0.5 mm, and the spinneret is extruded into fibers under a nitrogen pressure of 0.15-0.40 MPa.
[0021] According to the above-mentioned method for preparing melamine-polyimide composite fibers by dry spinning, the temperature of the hot air in the spinning tunnel in step c is 180-250° C., and the winding speed of the winding machine is 5-30 m / min.
[0022] According to the above-mentioned method for preparing melamine-polyimide composite fibers by dry spinning, the specific process of the imidization treatment in step c is: placing the obtained spun fibers in an oven for gradient heating, and the imidization treatment temperature is 50 to 220°C.
[0023] According to the above-mentioned method for preparing melamine-polyimide composite fibers by dry spinning, the specific treatment process when the imidization treatment temperature is 50-220°C is: heating to 50°C and keeping constant temperature for 0.5h, heating to 100°C and keeping constant temperature for 1h, heating to 150°C and keeping constant temperature for 1.5h, heating to 200°C and keeping constant temperature for 1h, heating to 220°C and keeping constant temperature for 0.5h.
[0024] The positive beneficial effects of the present invention are:
[0025] 1. The technical solution of the present invention aims to solve the problems of poor stability and spinnability of melamine resin, brittleness and poor toughness of melamine fiber and poor thermal stability at high temperature, and proposes to introduce polyimide as a modifier into melamine resin. By adding polyimide polymer chains, melamine has a branched and long molecular chain structure, thereby effectively reducing the steric hindrance of the triazine ring, improving the stability and spinnability of melamine resin, enhancing the toughness of melamine fiber, and having a high glass transition temperature, which can effectively improve the high-temperature thermal stability and flame retardancy of melamine fiber.
[0026] 2. The present invention belongs to the technical field of high-performance composite fiber manufacturing. The synergistic effect of melamine and polyimide makes the performance of the composite fiber better than melamine fiber and the cost lower than polyimide fiber. The primary fiber is prepared by dry spinning process, and the fiber surface is smooth and the inside is dense. The spinning process is simple, the winding speed is fast, and the production efficiency is high. The produced fiber can be used in various heat insulation and protection places, such as making fire suits, soldier protective clothing, steel workers' work clothes and high-temperature filter materials, aircraft wings and cabin door linings, etc. 4. Description of the drawings:
[0027] Figure 1 Infrared spectra of existing melamine fibers and the melamine-polyimide composite fibers prepared by the present invention;
[0028] Depend on Figure 1 By comparison, the composite fiber of the present invention has a -1 、1720cm -1 and 1379cm -1 There are obvious absorption peaks, namely the C=O asymmetric stretching vibration peak, the C=O symmetric stretching vibration peak and the CN stretching vibration peak on the polyimide imide ring, indicating the presence of imide rings in the composite fiber, that is, the present invention successfully introduces polyimide chain segments into the structure of melamine fibers.
[0029] Figure 2SEM image of the melamine-polyimide composite fiber prepared by the present invention;
[0030] Depend on Figure 2 SEM analysis shows that the composite fibers prepared in the present invention have uniform thickness and smooth surface, and the fiber cross section shows that the interior is dense and compact.
[0031] Figure 3 TG comparison diagram and partial magnified diagram of the melamine-polyimide composite fiber and melamine fiber prepared by the present invention;
[0032] Figure 3 In the figure, the curves respectively represent melamine fiber and composite fiber modified with polyamic acid salt prepared using different raw materials. By comparing the TG curves, it can be seen that the weight loss rate of the composite fiber is less than that of the melamine fiber at the same temperature, indicating that the introduction of polyimide in the composite fiber of the present invention achieves a good modification effect and enhances the thermal stability of the composite fiber.
[0033] Figure 4 A comparison chart of the limiting oxygen index (LOI) of the melamine-polyimide composite fiber and the melamine fiber prepared by the present invention;
[0034] Depend on Figure 4 From the comparison chart, it can be seen that the limiting oxygen index of the composite fibers prepared after polyimide modification increases to varying degrees, indicating that polyimide can effectively enhance the flame retardancy of the composite fibers.
[0035] Figure 5 A comparison chart of the mechanical properties of the melamine-polyimide composite fiber and the melamine fiber prepared by the present invention;
[0036] The mechanical properties of fibers are mainly judged by their breaking strength and breaking elongation. Figure 5 As can be seen from the comparison chart, the breaking strength and breaking elongation of the composite fiber prepared by the present invention are greater than those of the melamine fiber, indicating that polyimide can effectively improve the mechanical properties of the composite fiber. V. Specific implementation methods:
[0037] The present invention is further described below in conjunction with embodiments, but the protection scope of the technical solution of the present invention is not limited thereto.
[0038] The analysis and testing methods adopted in the following embodiments of the present invention are as follows:
[0039] 1) FT-IR analysis: The FT-IR200 Fourier transform infrared spectrometer of Nicolet Company of the United States was used, and the potassium bromide tablet method was used at 500-4000 cm -1 Perform a scan test within the range.
[0040] 2) SEM analysis: A scanning electron microscope SU8010 produced by HITACHI of Japan was used to observe the morphology of the melamine-polyimide composite fiber after surface spraying with gold under vacuum conditions and an accelerating voltage of 5KV.
[0041] 3) TG analysis: The thermal weight loss of the fiber was analyzed using a DTG-60 analyzer. 2 to 5 mg of the melamine-polyimide composite fiber prepared in the present invention was weighed. The temperature was raised from room temperature to 600° C. at a heating rate of 10° C. / min in a nitrogen atmosphere.
[0042] 4) Limiting oxygen index analysis: The limiting oxygen index of the fiber is tested according to FZ / T 50017-2011.
[0043] 5) Mechanical properties analysis: The fiber breaking strength and breaking elongation were tested using a YG006 single fiber strength tester.
[0044] Comparative Example:
[0045] A method for preparing melamine fiber by dry spinning, the detailed steps are as follows:
[0046] a. 90.00 g of melamine, 53.57 g of paraformaldehyde and 47.86 g of deionized water were added to a reactor, wherein the deionized water accounted for 25% of the total mass of the reaction system. The reaction temperature was controlled to be 85-95° C. At the same time, 0.75 g of a 20% sodium hydroxide aqueous solution was added to adjust the pH of the reaction solution to 8-9. After the reaction solution was clarified, the reaction was continued for 20 min. After the reaction was completed, the temperature was cooled in an ice water bath to obtain a melamine resin spinning solution.
[0047] b. The spinning solution was allowed to stand for degassing at a vacuum degree of 0.04 MPa, and then added into the feed liquid kettle of the dry spinning machine. The speed of the metering pump was 35 r / min. Under a nitrogen pressure of 0.20 MPa, the melamine resin spinning solution was extruded into fibers through a 0.30 mm spinneret and entered the spinning tunnel to remove solvent and water. The hot air temperature in the spinning tunnel was 180°C, and the winding speed of the winding machine was 15 m / min. The melamine primary fiber was obtained. The fiber was placed in an oven and cured under a nitrogen atmosphere. The specific heating process was as follows: heating to 50°C and keeping constant temperature for 0.5 h, heating to 100°C and keeping constant temperature for 1 h, heating to 150°C and keeping constant temperature for 1.5 h, heating to 200°C and keeping constant temperature for 1 h, and heating to 220°C and keeping constant temperature for 0.5 h. After treatment, the fiber was naturally cooled to room temperature in the oven to obtain melamine fiber.
[0048] The performance of the melamine fiber obtained in this comparative example was tested according to the above analysis and testing method: the temperature at which the melamine fiber loses 5% of its weight (T 5% ) is 223.04℃, and the temperature of 10% weight loss (T 10% ) is 277.59℃, the temperature of weight loss of 15% (T15% ) is 326.58℃, the single fiber breaking strength is 1.30cN / dtex, the breaking elongation is 3.78%, and the limiting oxygen index is 29%.
[0049] Embodiment 1:
[0050] The present invention provides a method for preparing melamine-polyimide composite fibers by dry spinning, and the detailed steps are as follows:
[0051] a. Dissolve 38.05 g of 3,4'-diaminodiphenyl ether in 410.04 g of NN dimethylformamide. After the reaction solution is clarified, add 64.45 g of 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride to continue the reaction. The reaction temperature is 0°C and the reaction time is 15 min. After the reaction, add 1.14 g of melamine and continue the reaction at this temperature for 2 h. Then add triethylamine to make the reaction solution undergo salt-forming reaction. Adjust the pH value of the reaction solution to 8. Continue the reaction for 1 h to obtain a water-soluble polyamic acid salt (PAAS-1) solution.
[0052] b. 30 g of melamine, 16.43 g of paraformaldehyde and 15.48 g of deionized water are added to a reactor, wherein the deionized water accounts for 25% of the total mass of the reaction system. At the same time, 0.25 g of a 20% sodium hydroxide aqueous solution is added, and the pH of the reaction solution is adjusted to 8. The reaction is heated to a reaction temperature of 85 to 95° C. and the reaction is carried out. After the reaction solution reaches a clear state for 15 minutes, a melamine resin is obtained. Then, the water-soluble polyamic acid salt (PAAS-1) solution obtained in step a is added according to a ratio of melamine to polyimide effective components of 9:1, and the reaction is continued at 85 to 95° C. for 10 minutes. After the reaction is completed, the temperature is cooled in an ice water bath to obtain a melamine-polyimide spinning solution.
[0053] c. The spinning solution obtained in step b was placed under a vacuum degree of 0.04 MPa for degassing. After degassing, it was added into the feed liquid kettle of the dry spinning machine. The speed of the metering pump was 30 r / min. Under a nitrogen pressure of 0.15 MPa, the spinning solution was extruded into fibers through a 0.10 mm spinneret. The fibers entered the spinning tunnel. The solvent NN dimethylformamide and water were removed. The hot air temperature in the spinning tunnel was 190°C. The fibers were then wound by a take-up machine at a winding speed of 5 m / min to obtain a dense The melamine-polyimide spun fibers were placed in an oven under a nitrogen atmosphere for imidization treatment. The specific treatment process was as follows: heating to 50°C and keeping constant temperature for 0.5h, heating to 100°C and keeping constant temperature for 1h, heating to 150°C and keeping constant temperature for 1.5h, heating to 200°C and keeping constant temperature for 1h, and heating to 220°C and keeping constant temperature for 0.5h. After treatment, the fibers were naturally cooled to room temperature in the oven and then taken out to obtain melamine-polyimide composite fibers (MF-PI-1).
[0054] The performance of the melamine-polyimide composite fiber MF-PI-1 obtained in this example was tested according to the above analysis and testing method: the temperature (T 5% ) is 249.67℃, the temperature of 10% weight loss (T 10% ) is 306.02℃, the temperature of weight loss of 15% (T 15% ) is 333.36℃, the single fiber breaking strength is 3.60cN / dtex, the breaking elongation is 8.53%, and the limiting oxygen index is 31.83%.
[0055] Embodiment 2:
[0056] The present invention provides a method for preparing melamine-polyimide composite fibers by dry spinning, and the detailed steps are as follows:
[0057] a. Dissolve 38.05 g of 4,4'-diaminodiphenyl ether in 347.56 g of NN dimethylacetamide. After the reaction solution is clarified, add 58.84 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride to continue the reaction. The reaction temperature is 0°C and the reaction time is 15 min. After the reaction, add 1.14 g of melamine and continue the reaction at this temperature for 2 h. Then add triethanolamine to make the reaction solution undergo a salt-forming reaction. Adjust the pH of the reaction solution to 9 and continue the reaction for 1 h. After the reaction, a water-soluble polyamic acid salt (PAAS-2) solution is obtained.
[0058] b. Add 30g of melamine, 17.14g of paraformaldehyde and 16.56g of deionized water into a reactor, wherein the deionized water accounts for 26% of the total mass of the reaction system. At the same time, add 0.25g of a 21% sodium hydroxide aqueous solution, adjust the pH of the reaction solution to 9, and then heat it to 85-95°C for reaction. After 15 minutes when the reaction solution reaches a clear state, a melamine resin is obtained. Then, the water-soluble polyamic acid salt solution obtained in step a is added according to a ratio of melamine resin to polyimide effective components of 8:2, and the reaction is continued at 85-95°C for 10 minutes. After the reaction is completed, cool it in an ice water bath to obtain a melamine-polyimide spinning solution.
[0059] c. The spinning solution obtained in step b is placed under a vacuum degree of 0.05 MPa for degassing. After degassing, it is added into the feed liquid kettle of the dry spinning machine. The metering pump speed is 32 r / min. Under a nitrogen pressure of 0.20 MPa, the spinning solution is extruded into fibers through a 0.20 mm spinneret. The fibers enter the spinning tunnel to remove the solvent NN dimethylacetamide and water. The hot air temperature in the spinning tunnel is 200°C. The fibers are then wound by a take-up machine at a winding speed of 10 m / min. The melamine-polyimide nascent fibers were obtained, and the nascent fibers were placed in an oven under a nitrogen atmosphere for imidization treatment. The specific treatment process was as follows: heating to 50°C and keeping constant temperature for 0.5 h, heating to 100°C and keeping constant temperature for 1 h, heating to 150°C and keeping constant temperature for 1.5 h, heating to 200°C and keeping constant temperature for 1 h, and heating to 220°C and keeping constant temperature for 0.5 h. After treatment, the fibers were naturally cooled to room temperature in the oven and taken out to obtain melamine-polyimide composite fibers (MF-PI-2).
[0060] The performance of the composite fiber MF-PI-2 obtained in this example was tested according to the above analysis and testing methods: the temperature at which MF-PI-2 loses 5% of its weight (T 5% ) is 291.75℃, the temperature of 10% weight loss (T 10% ) is 330.12℃, the temperature of weight loss of 15% (T 15% ) is 346.37℃, the single fiber breaking strength is 1.80cN / dtex, the breaking elongation is 6.03%, and the limiting oxygen index is 33.61%.
[0061] Embodiment 3:
[0062] The present invention provides a method for preparing melamine-polyimide composite fibers by dry spinning, and the detailed steps are as follows:
[0063] a. Dissolve 20.55 g of p-phenylenediamine in 265.15 g of N-methylpyrrolidone. After the reaction solution is clarified, add 62.04 g of 4,4'-biphenyl ether dianhydride to continue the reaction. The reaction temperature is 0°C and the reaction time is 15 min. After the reaction, add 1.14 g of melamine and continue the reaction at this temperature for 2 h. Then, add ammonia water to make the reaction solution undergo a salt-forming reaction. Adjust the pH of the reaction solution to 8.5. Continue the reaction for 1 h to obtain a water-soluble polyamic acid salt (PAAS-3) solution.
[0064] b. Add 30g of melamine, 17.86g of paraformaldehyde and 17.70g of deionized water into a reactor, wherein the deionized water accounts for 27% of the total mass of the reaction system. At the same time, add 0.25g of a 22% sodium hydroxide aqueous solution by mass, adjust the pH of the reaction solution to 8.5, and then heat it to a reaction temperature of 85-95°C for reaction. After 15 minutes when the reaction solution reaches a clear state, a melamine resin is obtained; then, the water-soluble polyamic acid salt solution obtained in step a is added according to a ratio of 7:3 between the effective components of the melamine resin and the polyimide, and the reaction is continued at 85-95°C for 10 minutes. After the reaction is completed, cool it in an ice water bath to obtain a melamine-polyimide spinning solution;
[0065] c. The spinning solution obtained in step b is placed under a vacuum degree of 0.06 MPa for degassing. After degassing, it is added into the feed liquid kettle of the dry spinning machine. The metering pump speed is 34 r / min. Under a nitrogen pressure of 0.25 MPa, the spinning solution is extruded into fibers through a 0.30 mm spinneret. The spinning solution enters the spinning tunnel to remove the solvent N-methylpyrrolidone and water. The hot air temperature in the spinning tunnel is 220°C. The spinning solution is then wound by a take-up machine at a winding speed of 15 m / min. The melamine-polyimide nascent fiber was obtained, and the nascent fiber was placed in an oven for imidization treatment under a nitrogen atmosphere. The specific treatment process was as follows: heating to 50°C and keeping constant temperature for 0.5h, heating to 100°C and keeping constant temperature for 1h, heating to 150°C and keeping constant temperature for 1.5h, heating to 200°C and keeping constant temperature for 1h, heating to 220°C and keeping constant temperature for 0.5h. After treatment, the fiber was naturally cooled to room temperature in the oven and taken out to obtain melamine-polyimide composite fiber (MF-PI-3).
[0066] The performance of the composite fiber MF-PI-3 obtained in this example was tested according to the above analysis and testing methods: the temperature at which MF-PI-3 loses 5% of its weight (T 5% ) is 267.71℃, the temperature of 10% weight loss (T 10% ) is 315.49℃, the temperature of weight loss of 15% (T 15% ) is 334.62℃, the single fiber breaking strength is 3.33cN / dtex, the breaking elongation is 9.03%, and the limiting oxygen index is 32.94%.
[0067] Embodiment 4:
[0068] The present invention provides a method for preparing melamine-polyimide composite fibers by dry spinning, and the detailed steps are as follows:
[0069] a. Dissolve 37.67 g of 4,4'-diaminodiphenylmethane in 234.61 g of dimethyl sulfoxide. After the reaction solution is clarified, add 43.62 g of pyromellitic anhydride to continue the reaction. The reaction temperature is 0°C and the reaction time is 15 min. Then add 1.14 g of melamine and continue the reaction at this temperature for 2 h. Add triethylamine to make the reaction solution undergo a salt-forming reaction. Adjust the pH of the reaction solution to 8. Continue the reaction for 1 h to obtain a water-soluble polyamic acid salt (PAAS-4) solution.
[0070] b. Add 30g of melamine, 18.57g of paraformaldehyde and 18.89g of deionized water into a reactor, wherein the deionized water accounts for 28% of the total mass of the reaction system. At the same time, add 0.25g of a 23% sodium hydroxide aqueous solution, adjust the pH of the reaction solution to 8, heat it to a reaction temperature of 85-95°C for reaction, and obtain melamine resin 15 minutes after the reaction solution reaches a clear state; add the water-soluble polyamic acid salt solution obtained in step a according to a ratio of melamine resin to polyimide effective components of 9:1, continue to react at 85-95°C for 10 minutes, and cool it in an ice water bath after the reaction is completed to obtain a melamine-polyimide spinning solution;
[0071] c. The spinning solution was placed in a vacuum of 0.04MPa for degassing. After degassing, it was added into the feed liquid kettle of the dry spinning machine. The metering pump speed was 36r / min. Under the nitrogen pressure of 0.30MPa, the spinning solution was extruded into fibers through a 0.40mm spinneret and entered the spinning tunnel. The solvent dimethyl sulfoxide and water were removed. The hot air temperature in the spinning tunnel was 230℃. Then it was wound by a take-up machine at a winding speed of 20m / min to obtain melamine -polyimide nascent fiber, the nascent fiber is placed in an oven for imidization treatment under a nitrogen atmosphere, the specific treatment process is: heating to 50°C and keeping constant temperature for 0.5h, heating to 100°C and keeping constant temperature for 1h, heating to 150°C and keeping constant temperature for 1.5h, heating to 200°C and keeping constant temperature for 1h, heating to 250°C and keeping constant temperature for 0.5h, after treatment, naturally cool to room temperature in the oven, take out, and obtain melamine-polyimide composite fiber (MF-PI-4).
[0072] The performance of the composite fiber MF-PI-4 obtained in this example was tested according to the above analysis and testing method: the temperature at which MF-PI-4 loses 5% of its weight (T 5% ) is 260.12℃, the temperature of 10% weight loss (T 10% ) is 309.59℃, the temperature of weight loss of 15% (T 15% ) is 327.72℃, the single fiber breaking strength is 3.45cN / dtex, the breaking elongation is 6.20%, and the limiting oxygen index is 32.37%.
[0073] Embodiment 5:
[0074] The present invention provides a method for preparing melamine-polyimide composite fibers by dry spinning, and the detailed steps are as follows:
[0075] a. Dissolve 20.55 g of m-phenylenediamine in 156.83 g of NN dimethylacetamide. After the reaction solution is clarified, add 39.63 g of 1,2,3,4-butanetetracarboxylic dianhydride to continue the reaction. The reaction temperature is 0 ° C. The reaction time is 15 min. Then, add 1.14 g of melamine. Continue to react at this temperature for 2 h. Then, add triethanolamine to make the reaction solution undergo salt-forming reaction. Adjust the pH of the reaction solution to 9. Continue to react for 1 h to obtain a water-soluble polyamic acid salt (PAAS-5) solution.
[0076] b. Add 30g of melamine, 19.29g of paraformaldehyde and 20.13g of deionized water into a reactor, wherein the deionized water accounts for 29% of the total mass of the reaction system. At the same time, add 0.25g of a 24% sodium hydroxide aqueous solution, adjust the pH of the reaction solution to 8.5, and then heat it to 85-95°C for reaction. After 15 minutes when the reaction solution reaches a clear state, a melamine resin is obtained. Add the water-soluble polyamic acid salt solution obtained in step a according to the effective component ratio of melamine resin to polyimide of 8:2, continue to react at 85-95°C for 10 minutes, and cool it in an ice water bath after the reaction is completed to obtain a melamine-polyimide spinning solution.
[0077] c. The spinning solution was placed in a vacuum of 0.05 MPa for degassing. After degassing, it was added into the feed liquid kettle of the dry spinning machine. The metering pump speed was 38 r / min. Under the nitrogen pressure of 0.35 MPa, the spinning solution was extruded into fibers through a 0.50 mm spinneret. The fibers entered the spinning tunnel to remove the solvent NN dimethylacetamide and water. The hot air temperature in the spinning tunnel was 240°C. The fibers were then wound by a take-up machine at a winding speed of 25 m / min. The melamine-polyimide nascent fiber is placed in an oven for imidization treatment under a nitrogen atmosphere. The specific treatment process is: heating to 50°C and keeping constant temperature for 0.5h, heating to 100°C and keeping constant temperature for 1h, heating to 150°C and keeping constant temperature for 1.5h, heating to 200°C and keeping constant temperature for 1h, heating to 220°C and keeping constant temperature for 0.5h. After treatment, the fiber is naturally cooled to room temperature in the oven and taken out to obtain melamine-polyimide composite fiber (MF-PI-5).
[0078] The performance of the composite fiber MF-PI-5 obtained in this example was tested according to the above analysis and testing method: the temperature at which MF-PI-5 loses 5% of its weight (T 5% ) is 246.31℃, and the temperature of 10% weight loss (T 10% ) is 311.59℃, the temperature of weight loss of 15% (T 15%) is 336.41℃, the single fiber breaking strength is 4.28cN / dtex, the breaking elongation is 6.75%, and the limiting oxygen index is 31.27%.
[0079] Embodiment 6:
[0080] The present invention provides a method for preparing melamine-polyimide composite fibers by dry spinning, and the detailed steps are as follows:
[0081] a. Dissolve 20.55 g of o-phenylenediamine in 217.82 g of NN dimethylformamide. After the reaction solution is clarified, add 71.66 g of 3,3,4,4-diphenylsulfone tetracarboxylic acid dianhydride to continue the reaction. The reaction temperature is 0 ° C. and the reaction time is 15 min. After the reaction, add 1.14 g of melamine. Continue to react at this temperature for 2 h. Then add ammonia water to make the reaction solution undergo salt-forming reaction. Adjust the pH of the reaction solution to 8. Continue to react for 1 h to obtain a water-soluble polyamic acid salt (PAAS-6) solution.
[0082] b. Add 30g of melamine, 20.00g of paraformaldehyde and 21.43g of deionized water into a reactor, wherein the deionized water accounts for 30% of the total mass of the reaction system. At the same time, add 0.25g of a 25% sodium hydroxide aqueous solution, adjust the pH of the reaction solution to 9, and then heat it to 85-95°C for reaction. After 15 minutes when the reaction solution reaches a clear state, a melamine resin is obtained. Then, the water-soluble polyamic acid salt solution obtained in step a is added according to a ratio of 7:3 between the effective components of the melamine resin and the polyimide, and the reaction is continued at 85-95°C for 10 minutes. After the reaction is completed, cool it in an ice water bath to obtain a melamine-polyimide spinning solution.
[0083] c. The spinning solution was placed under a vacuum degree of 0.06 MPa for degassing. After degassing, it was added into the feed liquid kettle of the dry spinning machine. The metering pump speed was 40 r / min. Under a nitrogen pressure of 0.40 MPa, the spinning solution was extruded into fibers through a 0.30 mm spinneret. The fibers entered the spinning tunnel. The solvent N-N-dimethylformamide and water were removed. The hot air temperature in the spinning tunnel was 250°C. The fibers were then wound by a take-up machine at a winding speed of 30 m / min. The melamine-polyimide nascent fiber is placed in an oven for imidization treatment under a nitrogen atmosphere. The specific treatment process is: heating to 50°C and keeping constant temperature for 0.5h, heating to 100°C and keeping constant temperature for 1h, heating to 150°C and keeping constant temperature for 1.5h, heating to 200°C and keeping constant temperature for 1h, heating to 220°C and keeping constant temperature for 0.5h. After treatment, the fiber is naturally cooled to room temperature in the oven and taken out to obtain melamine-polyimide composite fiber (MF-PI-6).
[0084] The performance of the composite fiber MF-PI-6 obtained in this example was tested according to the above analysis and testing method: the temperature at which MF-PI-6 loses 5% of its weight (T5% ) is 249.54℃, and the temperature of 10% weight loss (T 10% ) is 305.36℃, the temperature of weight loss of 15% (T 15% ) is 338.99℃, the single fiber breaking strength is 1.85cN / dtex, the breaking elongation is 5.28%, and the limiting oxygen index is 31.52%.
[0085] The temperature changes of the melamine fiber prepared in the comparative example and the melamine-polyimide composite fiber prepared in the example of the present invention at the same weight loss rate are shown in Table 1.
[0086] Table 1 Temperature changes of melamine fiber MF obtained in comparative example and composite fiber prepared in example of the present invention at the same weight loss rate
[0087]
[0088] It can be seen from Table 1 that the temperature resistance of the composite fiber prepared by the present invention changes. The modification method is analyzed by taking the MF-PI-B2 fiber with better temperature resistance improvement effect as an example: compared with the temperature at which the melamine fiber loses 5%, 10%, and 15%, the temperature resistance of the MF-PI-B2 fiber is improved by 68.71°C, 52.53°C, and 19.79°C respectively at the same weight loss rate. This is mainly because the polyamic acid salt is added during the reaction process of the melamine resin, and the polyamic acid salt is terminated with melamine. Under heating conditions, the melamine in the polyamic acid salt reacts with the polyformaldehyde in the melamine resin, and the two systems further polycondense and crosslink, and a small part of the structure in the polyamic acid salt is dehydrated to form an imide ring. The chemical reaction method changes the molecular chain structure of the melamine resin in the process of preparing the spinning solution. In the later high-temperature imidization process, the fiber is further dehydrated and crosslinked, so that the temperature resistance of the composite fiber is greatly improved.
Claims
1. A method for preparing melamine-polyimide composite fibers by dry spinning, characterized in that: The preparation method comprises the following steps: a. Dissolve a diamine substance in an organic solvent, add a dianhydride substance after it is fully dissolved to react, control the reaction temperature to be 0°C, and the reaction time to be 10 to 30 minutes; add melamine after the reaction, and continue to react at the reaction temperature for 2 to 3 hours; then add a base to make the polyamic acid undergo a salt-forming reaction, adjust the pH of the resulting reaction solution to 8 to 9, and continue to react for 1 hour to obtain a water-soluble polyamic acid salt solution after the reaction; The diamine substance is at least one of 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, p-phenylenediamine, 4,4'-diaminodiphenylmethane, m-phenylenediamine and o-phenylenediamine; The dianhydride substance is at least one of 3, 3', 4, 4'-benzophenone tetracarboxylic dianhydride, 3, 3', 4, 4'-biphenyl tetracarboxylic dianhydride, 4, 4'-biphenyl ether dianhydride, pyromellitic dianhydride, 1, 2, 3, 4-butane tetracarboxylic dianhydride and 3, 3, 4, 4-diphenyl sulfone tetracarboxylic dianhydride; The molar ratio between the amino group (-NH2) of diamine substances, the amino group (-NH2) in melamine and the anhydride (R-CO-O-CO-R') in dianhydride substances is 0.95-0.97:0.07-0.09:1; b. Add melamine, paraformaldehyde and deionized water into a reactor, and add sodium hydroxide aqueous solution to adjust the pH of the reaction solution to 8-9, and then heat to 85-95° C. for reaction. After the reaction solution reaches a clear state, 5-20 minutes later, a melamine resin is obtained; then, the water-soluble polyamic acid salt solution obtained in step a is added according to the mass ratio of melamine resin to polyamic acid salt effective component of 7-9:1-3, and the reaction is continued at this temperature for 10-20 minutes. After the reaction is completed, the temperature is cooled in an ice water bath to obtain a melamine-polyimide spinning solution; c. Degassing the melamine-polyimide spinning solution obtained in step b, adding it into a dry spinning machine after degassing to extrude it into fibers through a spinneret, and then removing the solvent through hot air in the spinning tunnel and winding it with a fiber collecting machine to obtain melamine-polyimide nascent fibers; placing the obtained nascent fibers in an oven under nitrogen atmosphere for imidization treatment, and naturally cooling them to room temperature after treatment to obtain melamine-polyimide composite fibers.
2. The method for preparing melamine-polyimide composite fiber by dry spinning according to claim 1, characterized in that: The organic solvent in step a is any one of N-dimethylformamide, N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone; The base is at least one of triethylamine, aqueous ammonia and triethanolamine.
3. The method for preparing melamine-polyimide composite fiber by dry spinning according to claim 1, characterized in that: The amount of organic solvent added in step a accounts for 70-80% of the reaction system.
4. The method for preparing melamine-polyimide composite fiber by dry spinning according to claim 1, characterized in that: In step b, the molar ratio of melamine to paraformaldehyde is 1:2.3-2.8; the amount of deionized water added is 25-30% of the total mass of the reaction system; and the mass percentage concentration of the sodium hydroxide aqueous solution is 20-25%.
5. The method for preparing melamine-polyimide composite fiber by dry spinning according to claim 1, characterized in that: The degassing method in step c is vacuum static degassing, and the vacuum degree is 0.04-0.06MPa.
6. The method for preparing melamine-polyimide composite fiber by dry spinning according to claim 1, characterized in that: The rotation speed of the metering pump of the dry spinning machine in step c is 30-40 r / min.
7. The method for preparing melamine-polyimide composite fiber by dry spinning according to claim 1, characterized in that: The aperture of the spinneret in step c is 0.1-0.5 mm, and the condition for extruding the spinneret into fibers is a nitrogen pressure of 0.15-0.40 MPa.
8. The method for preparing melamine-polyimide composite fiber by dry spinning according to claim 1, characterized in that: In step c, the temperature of the hot air in the spinning tunnel is 180-250° C., and the winding speed of the winding machine is 5-30 m / min.
9. The method for preparing melamine-polyimide composite fiber by dry spinning according to claim 1, characterized in that: The specific process of the imidization treatment in step c is: placing the obtained as-spun fiber in an oven for gradient heating, and the imidization treatment temperature is 50-220°C.
10. The method for preparing melamine-polyimide composite fiber by dry spinning according to claim 9, characterized in that: The specific treatment process when the imidization treatment temperature is 50-220°C is: heating to 50°C and keeping constant temperature for 0.5h, heating to 100°C and keeping constant temperature for 1h, heating to 150°C and keeping constant temperature for 1.5h, heating to 200°C and keeping constant temperature for 1h, heating to 220°C and keeping constant temperature for 0.5h.
Citation Information
Patent Citations
Preparation method of novel composite melamine resin-polyimide foam
CN112175349A
Preparation method of high-temperature-resistant flame-retardant polyimide modified melamine oil-absorbing foam
CN113248777A